An application of hydrothermal process to treat palm oil mill effluent (POME) - Cheng, Chin Kui; Khan, Maksudur Rahman; Ruwaida, Abdul Rasid; Chin, Sim Yee; Asmida, Ideris; Herma Dina, Setiabudi (2013)
This study evaluates the effects of subcritical hydrothermal treatment on palm oil mill effluent (POME) and its concomitant formations of solid hydrochar, liquid product and gaseous product. The reactions were carried out at temperatures ranged 493 K-533 K for 2 h. The highest reduction of chemical oxygen demand (COD) and biochemical oxygen demand (BOD) were 58.8% and 62.5%, respectively, at 533 K. In addition, the removal of total suspended solids (TSS) achieved up to 99%, with the pH of POME reaching 6 from the initial pH 4. The gas chromatography coupled with mass spectroscopy (GC-MS) analysis showed that the fresh POME contained n-Hexadecanoic acid as the dominant component, which gradually reduced in the liquid product in the reaction with increased temperature, in addition to the attenuation of carboxyl compounds and elevation of phenolic components. The gaseous products contained C02, CO, H2, and C3 - C6 hydrocarbons. Traces of CH4 were only found at 533 K. C02 is the dominant species, where the highest of 3.99 val% per 500 ml working volume of POME recorded at 533 K. The solid hydrochars showed negligible morphological changes across the reaction temperature. The 0/C atomic ratio of the hydrochar range from 0.157 to 0.379, while the H/C atomic ratio was in the range from 0.930 to 1.506. With the increase of treatment temperature, the higher heating value (HHV) of the hydrochar improved from 24.624 to 27.513 MJ kg-1. The characteristics of hydrochar make it a fuel source with immense potential. POME decomposed into water-soluble compounds, followed by deoxygenation (dehydration and decarboxylation) in producing hydrochar with lower oxygen content and higher aromatic compounds in the liquid product. Little gaseous hydrocarbons were produced due to subcritical hydrothermal gasification at low temperature.